Eco-Smart Economics: Revolutionizing Jordan’s Logistics with Sustainable Drone Technology - Samawi, Ghazi A.; Bwaliez, Omar M.; Dmour, Wajd A.; Mdanat, Metri F.; Ta’Amnha, Mohammad A. (International Journal of Energy Economics and Policy, 2024)
This study explores the implications of sustainable drone technology on the development of Jordan’s logistics sector through the eco-smart economics lens. Based on in-depth qualitative data drawn from 42 semi-structured interviews conducted in Jordan, the study evaluates drones’ influences on environmental, operational, and economic processes, finding that drone technology has the potential to substantially improve delivery timeframes, diminish carbon emissions, and contribute to the sustainable development agenda. However, the study has also outlined several limitations, such as regulatory, technical, and public concerns, especially related to privacy and security. In this regard, for Jordan to benefit from drones in the logistics sector, policy, technological, and partnership advancements are required. Such changes would ensure that Jordan develops a sustainable, rapid, and efficient logistics sector to strengthen its economy.